Characterization of Hericium erinaceum powders prepared by conventional roll milling and jet milling. (January 2015) - Phat, Chanvorleak; Li, Hua; Lee, Dong-Un; Moon, BoKyung; Yoo, Young-Bok; Lee, Chan
Highlights: Jet-milled and roll-milled powders were prepared from the fruit body of Hericium erinaceum . Physicochemical properties were examined in both powders. Jet milling method enhanced physiochemical properties of H. erinaceum powders. The superfine grinding method of jet milling could provide more opportunities in food applications. Abstract: Four types of powder were prepared from freeze-dried fruiting bodies of the edible mushroom Hericium erinaceum by 2 different methods-conventional roll milling and the superfine grinding method of jet milling-at 3 different speeds, to compare their physicochemical properties and extraction of proteins and polysaccharides. Jet-milled powders prepared at 16, 000 rpm (JMP1), 9000 rpm (JMP2), and 5000 rpm (JMP3), and roll-milled powder (RMP) had an average particle size of 5.5, 12.9, 25.2, and 243.6 μm, respectively. The reduction of particle size resulted in increased specific surface area, porosity, and bulk density. Among the 4 powders, JMP1 showed the highest bulk density (0.17 g/ml). The water solubility index of H. erinaceum powder increased from 35.2% in RMP to 53.1% in JMP1. Similarly, the swelling capacity of JMP1, JMP2, JMP3, and RMP was 11.28 ml/g, 7.36 ml/g, 6.26 ml/g, and 5.9 ml/g, respectively. The extractions of proteins and polysaccharides from H. erinaceum powders were also improved by the application of jet milling. These results suggest that the superfine grinding method of jet milling could provide more opportunities for mushroom powders to be incorporated in a wider variety of functional food applications.